P134 Lung function in post-transplant Hodgkin's lymphoma patients. (16th November 2010) - McConkey, H; Sachchithanantham, S; Gillion, M; Raj, K; Kazmi, M; Fields, P; Streetly, M; Milburn, H
Abstract : Introduction: Pulmonary complications are a prominent cause of morbidity and mortality following stem cell transplant (SCT) accounting for more than 30% of transplantation-related deaths. Exposure to agents associated with pulmonary toxicity (bleomycin, radiotherapy) is common in patients with Hodgkins lymphoma (HL) for whom SCT is a standard approach at relapse, making them potentially more susceptible to pulmonary toxicity post-transplant. Sequential pulmonary function tests (PFTs), are sensitive measures of lung disease after SCT allowing early diagnosis and treatment, thereby improving outcome. We report a retrospective analysis of serial PFT monitoring of patients with relapsed HL who underwent SCT. Methods: Patients were assessed with serial PFTs pre (T=0) and post SCT (initially 6 weeks and then 3 monthly thereafter). Standardised PFTs were expressed as a percentage of the pre-transplant value (100%). Tests were carried out by the same personnel, to ensure standardisation and eliminate variability in patient performance. Results: 29 patients were studied with median age at SCT of 35.3 years (range 17.1–60.7 years). Pre-transplant conditioning utilised chemotherapy (predominantly BEAM—carmustine, etoposide, cytarabine, melphalan) for all except two transplants (TBI based). The median follow up was 18 months (range 3–117 months) and a median of four PFTs performed (range 2–16). FEV1 was decreased >10% in 13/29 and >20% in five of these patients, FVC was reduced >10% in 12/29 and >20% in 5/29. TLCO reduction >10% was observed in 21/29 and >20% in 13/29 and KCO decrease >10% occurred in 18/29 and >20% 9/29 patients. Reductions in TLCO/KCO occurred earlier than FEV1 /FVC reductions (median 1.5 and 3 months respectively). Recovery of lung function occurred in >50% of patients who had repeat investigation within 24 m. Significant reduction of TLCO/KCO was observed in only 1/10 patients who had PFTs >3 years from transplant (Abstract P134 Figure 1 ). Conclusion: PFTs initially deteriorated in a significant proportion of patients but tended to recover by 30–40 months post transplant. This could be due to pulmonary toxicity from conditioning therapy, post-transplant lung injury, or a combination of both. During the first 3 years post-transplant, patients have an increased risk of developing pulmonary complications providing a rationale for serial PFTs.